2020
DOI: 10.7554/elife.61821
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids modulate associative cerebellar learning via alterations in behavioral state

Abstract: Cannabinoids are notorious and profound modulators of behavioral state. In the brain, endocannabinoids act via Type 1-cannabinoid receptors (CB1) to modulate synaptic transmission and mediate multiple forms of synaptic plasticity. CB1 knockout (CB1KO) mice display a range of behavioral phenotypes, in particular hypoactivity and various deficits in learning and memory, including cerebellum-dependent delay eyeblink conditioning. Here we find that the apparent effects of CB1 deletion on cerebellar learning are no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(20 citation statements)
references
References 97 publications
0
20
0
Order By: Relevance
“…They utilised a similar PKG-neo recombination strategy, only replacing the coding region of the Cnr1 gene between amino acids 32 and 448. These chimeric mice were subsequently bred with C57BL/6J animals for more than 10 generations, resulting in mutants with a congenic C57BL/6J background [159][160][161][162]. Marsicano et al later generated a new CB1R-null mutant line using the Cre-lox system for site-directed recombination [163].…”
Section: Cb1r Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They utilised a similar PKG-neo recombination strategy, only replacing the coding region of the Cnr1 gene between amino acids 32 and 448. These chimeric mice were subsequently bred with C57BL/6J animals for more than 10 generations, resulting in mutants with a congenic C57BL/6J background [159][160][161][162]. Marsicano et al later generated a new CB1R-null mutant line using the Cre-lox system for site-directed recombination [163].…”
Section: Cb1r Mouse Modelsmentioning
confidence: 99%
“…Despite differences in mutation techniques and genetic backgrounds, these investigations have yielded similar and congruent results (Table 10). Overall, these mutant mice exhibited increased mortality and more severe seizures [142,164], anxietylike behaviours [153,155], reduced locomotor activity [142,162], accelerated cognitive decline [159][160][161][162], and impaired memory extinction processes [163,165,166]. Interestingly, CB1R was proven to be dispensable for memory extinction in appetite-motivated learning tasks, whereas it presumably plays a crucial role in fear extinction, primarily via habituation-like processes [166].…”
Section: Cb1r Mouse Modelsmentioning
confidence: 99%
“…Sex and strain are not the only variables that can potentially influence mice performance during delay eyeblink conditioning. This task is most commonly performed in head-fixed mice freely running on a wheel and studies have shown that locomotion speed on the wheel positively correlates with a higher percentage of CRs [ 27 , 28 ]. However, it is still unknown if locomotion strategy during delay eyeblink conditioning is sex dependent.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the cerebellum engages different functions for walking when two legs in human (or two sides of limbs in mice) move in the same versus different cycling speed. [1][2][3][4] This has been the foundation of cerebellar-based motor learning and rehabilitation after cerebral insults. 3,4 Adding to the complexity, most of the movement disorders behave very differently when volitional movement is involved.…”
Section: Introductionmentioning
confidence: 99%
“…However, many motor phenomena, such as reaching movement, walking, or balancing, involved complex coordinated movement beyond the limb being studied. For example, the cerebellum engages different functions for walking when two legs in human (or two sides of limbs in mice) move in the same versus different cycling speed 1–4 . This has been the foundation of cerebellar‐based motor learning and rehabilitation after cerebral insults 3,4 .…”
Section: Introductionmentioning
confidence: 99%